Histological Pattern of Ovarian Tumor in Reproductive age group in a Tertiary Care Hospital - Naila Qureshi, Fahmida Parveen Memon, Ambreen Mughal, (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives: To find out the frequency of histological pattern of ovarian tumor in reproductive age group in a tertiary care Hospital. Study Design: Cross sectional study. Place & duration of study: Department of Obstetrics & Gynecology, Liaquat University of medical and health sciences hospital, Hyderabad from October 2021 to September 2022. Methodology: All patients with ovarian tumor in reproductive age admitted during study periods were included in study. The diagnosis of ovarian tumors was suspected form clinical features and ultrasound findings and confirmed on histopathology. Data analysis was performed on SPSS version 24. Chi-Square test of significance (chi square test) was applied to see association among categorical variables. P value ≤ 0.05 was taken as significant. Results: Similarly pattern of ovarian tumors was as followed; such as cord stromal, germ cell and epithelial ovarian 50%, 33.96% and 16.04% respectively among 106 women. High incidence of sex cord and epithelial tumors was observed in older age (above 40 years) group 25% and 68.8% respectively but germ cell tumor was observed mostly in younger age group 92.6% in 21-30 years as compared to older age women and 6.3% in above 40 years. Practical Implication: Our research establishes the basis for future studies on ovarian tumor in Pakistan, allowing for better health policy decisions to be made based on this information. Conclusion: Histopathological examination shows that epithelial and germ cell tumors collectively constitute large number of cases specifically in older age. Histological examination in early stage of life is important therapeutically and prognostically. Keywords: Ovarian tumors, Malignancies, Histological pattern, Reproductive age, Parity